Transcutaneous Nerve Electrostimulation (TENS) in Pain Relief During Labor: A Scope Review - Reis, Carla Cristina Silveira dos; Dias, Leandro da Cunha; Carvalho, Lorena Bezerra; Junior, Lourivaldo Bispo Alves; Imoto, Aline Mizusaki (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2022)
Objective To map health evidence on the effectiveness of transcutaneous nerve electrostimulation (TENS) therapy in pain relief during delivery.Methods This is a scoping review in the PubMed, LILACS, Cochrane, VHL, PEDRO, and SciELO databases, through the descriptors electric stimulation, transcutaneous and labor, obstetric and their synonyms.Results A total of 263 studies were identified, of which 54 duplicates were excluded. After sorting by titles and abstracts, there were 24 articles for reading, remaining 6. The six studies evaluated the reduction of pain through the visual analogue scale (VAS).Conclusion The findings indicate that the use of TENS as a nonpharmacological strategy for pain relief in labor has positive results.
Keywords: transcutaneous nervous electrical stimulation; labor pain; birth work